Pesquisa em nanotecnologia para o agronegócio: indicadores bibliométricos de produção científica entre 2001 e 2010 - Puerta, Adriana Aparecida (Universidade Federal de São Carlos, 2012)
Agribusiness is one of the most important segments of the global economy and national levels. The success of Brazilian agribusiness is due, among other factors, the increased productivity achieved by the incorporation of a number of technologies. Currently, it is believed that nanotechnology has enormous potential to positively impact the agribusiness, which has led to major efforts and investments in research and development in this area. Because nanotechnology and its application to agribusiness a recent area of research and dynamic, for better targeting of national research studies are needed on production for greater scientific knowledge about the advances that have occurred in the area. The objective of this study was to understand the current situation of international scientific research on nanotechnology for agribusiness, especially the position of Brazil. The bibliometrics was adopted as a quantitative method of analyzing information for the preparation of scientific indicators. The bibliographic records of scientific papers on nanotechnology for agribusiness, published between 2001 and 2010 were retrieved from the databases Web of Science (multidisciplinary) and CAB Abstracts (specializing in Agricultural Sciences). For quantification of the publications was used VantagePoint software. Indicators were constructed featuring publications by year, country, author, institution, field of knowledge, periodic and subject to data extracted from two databases, detailed for Brazil and for the subject sensors. During the period, 2057 articles were retrieved in Web of Science and 14,873 articles in Cab Abstracts. The growth of scientific production during the 10 years of study was significant and consistent. The results indicate that the United States, China and India are the leaders in research, with Brazil accounting for about 4.2% of total publications in Web of Science (8 th) and 3.9% in Cab Abstracts (5th position) . The graphics of authors and institutions reinforce the dominance of the United States and China in the area. As for Brazil, it is noted that most authors binds to institutions located in São Paulo, with emphasis on the USP, Embrapa, UFSCar and Unicamp, indicating the centrality of research in Brazil. With regard to areas of knowledge, Web of Science publications focus primarily on Analytical Chemistry and Environmental Sciences. In Cab Abstracts, cabicodes the most prominent were: ZZ900 - Techniques and Methodology and PP200 - Water Resources. The issues highlighted were: Pesticides, Water, Sensors and Biosensors, Food and Soil. The journals with the highest number of publications on the topics were: Biosensors and Bioelectronics, Environmental Science & Technology, Analytica Chimica Acta and Journal of Hazardous Materials. The results contribute to the construction of scientific knowledge in nanotechnology for agribusiness, and bibliometrics an essential tool to quantify the results of science in any field of knowledge. The research highlights the importance of conducting exploratory research different complementary databases, including specialized databases, to circumvent the limitations and weaknesses inherent in the sources of information more widely used for the analysis of scientific production.
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Nanotecnologia; Agronegócio; Indicadores científicos; Bibliometria; Nanotechnology; Agribusiness; Bibliometrics; Scientific indicators; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO